(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
It is a case of robbery and strangulation. Three unknown persons entered in the house of deceased for the purpose of robbery. The deceased and her daughter were present in the house at the time of incident. First the robbers tied both the persons and then looted cash and articles worth one lakh Rupees. When the deceased tried to resist and shouted for help she was strangled in front of her daughter. The strangulation is done by soft ligature material. We conducted the post-mortem examination at 9.55 A.M. on 10.6.03. We found prominent muscle contractions involving muscles of the neck namely, anterior belly of digastric, sternal and clavicular bands of sternocleidomastoid, and platysma. This prominence was seen at the root as well as at the top of the neck.